PROFITABILITAS PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Andri Andri; Amir Hasan; Teddy Chandra (Jurnal Ekonomi, 2015)
The Objective of this research are to analyze the Firm Size, CAR, NPL, NIM,BOPO, LDR and GWM with profitability (ROA). The Population of the researchare 20 banks that is listed at the Indonesia Stock Exchange and published per 31stDecember for year 2004-2008. Multiple Regression Analysis is used to determinerelationship and influence between dependent variable and independent variable.According to research result in 20 banks that listed at Indonesia Stock Exchangeperiod 2004-2008. It could be concluded that influence independent variable(Firm Size, CAR, NPL, NM, BOPO, LDR and GWM) with dependent variable(ROA). It indicated from value of Fobs is large than Ftable (Fobs = 53.361 > Ftable =2.11077) with probability (p) = 0.00000 is smaller than 0.05. The figure, inhypotesis nul is rejected meaning independent variable can gives simultant has aninfluence and significant with dependent variable.Determination coeficient (adjR2) value 78.7%, it means than an independent variable can give simultantcontribution to dependent variable about 78.7% on the otherhand 21.3% isinfluenced by another variable. A Partially (individual test) show that fiveindependent variable (firm size, Car, NPL, NIM, BOPO) have significant withdependent variable(ROA) because Tobs is large than Ttable and probability (p) issmaller than 0.05. Two independent variable (LDR and GWM) do not havesignificant influence with dependent variable (ROA) because Tobs is smaller thanTtable and probability (p) is large than 0.05